Accidents at level crossings in Cuba during the period from 1991 to 2007 - Villaroel Castro, José (2025)
In this study, the relation between the accidents in level crossings and those of regular traffic is established, as well as the main causes of their variation in the period between 1991 and 2007.  An analysis of accidents in this period was carried out, regarding the hours of higher accident risk, the amount of dead and wounded people, the vehicles that cause the highest amounts of collisions, and the provinces and the lines with the highest accident rates. Besides that, some measures to improve the security in level crossings that exist in Cuba are proposed.